Mobilization of endothelial progenitor cells in acute cardiovascular events in the PROCELL study: Time-course after acute myocardial infarction and stroke. (March 2015) - Regueiro, Ander; Cuadrado-Godia, Elisa; Bueno-Betí, Carlos; Diaz-Ricart, Maribel; Oliveras, Anna; Novella, Susana; Gené, Gemma González; Jung, Carole; Subirana, Isaac; Ortiz-Pérez, Jose Tomás; Roqué, Mercè; Freixa, Xavier; et al.
Abstract: The mobilization pattern and functionality of endothelial progenitor cells after an acute ischemic event remain largely unknown. The aim of our study was to characterize and compare the short- and long-term mobilization of endothelial progenitor cells and circulating endothelial cells after acute myocardial infarction or atherothrombotic stroke, and to determine the relationship between these cell counts and plasma concentrations of vascular cell adhesion molecule (VCAM-1) and Von Willebrand factor (VWF) as surrogate markers of endothelial damage and inflammation. In addition, we assessed whether endothelial progenitor cells behave like functional endothelial cells. We included 150 patients with acute myocardial infarction or atherothrombotic stroke and 145 controls. Endothelial progenitor cells [CD45 −, CD34 +, KDR +, CD133 +], circulating endothelial cells [CD45 −, CD146 +, CD31 +], VWF, and VCAM-1 levels were measured in controls (baseline only) and in patients within 24 h (baseline) and at 7, 30, and 180 days after the event. Myocardial infarction patients had higher counts of endothelial progenitor cells and circulating endothelial cells than the controls (201.0/mL vs. 57.0/mL; p < 0.01 and 181.0/mL vs. 62.0/mL; p < 0.01). Endothelial progenitor cells peaked at 30 days post-infarction (201.0/mL vs. 369.5/mL; p < 0.01), as did VCAM-1 (573.7 ng/mL vs. 701.8 ng/mL; p < 0.01). At 180 days post-infarction, circulating endothelial cells and VWF decreased, compared to baseline. In stroke patients, the number of endothelial progenitor cells — but not circulating endothelial cells — was higher than in controls (90.0/mL vs. 37.0/mL; p = 0.01; 105.0/mL vs. 71.0/mL; p = 0.11). At 30 days after stroke, however, VCAM-1 peaked (628.1/mL vs. 869.1/mL; p < 0.01) but there was no significant change in endothelial progenitor cells (90/mL vs. 78/mL; p < 0.34). At 180 days after stroke, circulating endothelial cells and VWF decreased, compared to baseline. Cultured endothelial progenitor cells from controls and myocardial infarction patients had endothelial phenotype characteristics and exhibited functional differences in adhesion and Ca 2 + influx, but not in proliferation and vasculogenesis. In myocardial infarction patients, VCAM-1 levels and mobilization of endothelial progenitor cells peaked at 30 days after the ischemic event. Although a similar VCAM-1 kinetic was observed in stroke patients, endothelial progenitor cells did not increase. Endothelial progenitor cells had mature endothelial capabilities in vitro. Highlights: EPC and CEC counts were higher in AMI and stroke patients than in controls. EPC mobilization and VCAM-1 peaked at 30 days after an AMI. After stroke, VCAM-1 peaked at 30 days without a peak in EPCs. Cultured EPCs had a mature endothelial capability. Functionality of cultured EPCs from AMI patients was enhanced compared to controls.